Management of acute COPD exacerbations in Australia: do we follow the guidelines?. Issue 2 (19th April 2020) - Cousins, Joyce L.; Wood-Baker, Richard; Wark, Peter A.B.; Yang, Ian A.; Gibson, Peter G.; Hutchinson, Anastasia; Sajkov, Dimitar; Hiles, Sarah A.; Samuel, Sameh; McDonald, Vanessa M.
Objective: We aimed to assess adherence to the Australian national guideline (COPD-X) against audited practice, and to document the outcomes of patients hospitalised with an acute exacerbation of chronic obstructive pulmonary disease (COPD) at discharge and 28 days after. Methods: A prospective clinical audit of COPD hospital admission from five tertiary care hospitals in five states of Australia was conducted. Post-discharge follow-up was conducted via telephone to assess for readmission and health status. Results: There were 207 admissions for acute exacerbation (171 patients; mean 70.2 years old; 50.3% males). Readmission rates at 28 days were 25.4%, with one (0.6%) death during admission and eight (6.1%) post-discharge within 28 days. Concordance to the COPD-X guidance was variable; 22.7% performed spirometry, 81.1% had blood gases collected when forced expiratory volume in 1 s was <1 L, 99.5% had chest radiography performed, 95.1% were prescribed systemic corticosteroids and 95% were prescribed antibiotic therapy. There were 89.1% given oxygen therapy and 92.6% when arterial oxygen tension was <80 mmHg; 65.6% were given ventilatory assistance when pH was <7.35. Only 32.4% were referred to pulmonary rehabilitation but 76.8% had general practitioner follow-up arranged. Conclusion: When compared against clinical practice guidelines, we found important gaps in management of patients admitted with COPD throughout tertiary care centres in Australia. Strategies to improve guideline uptake are needed to optimise care. A multisite audit of hospital admissions for patients experiencing #AECOPD in Australia highlighted important gaps in management when compared against national guidelines. Further focus on how we can improve guideline uptake by clinicians is needed. http://bit.ly/2VjGnHw